F16. INFLAMMATORY MARKERS ARE ASSOCIATED WITH PSYCHOMOTOR SLOWING IN PATIENTS WITH SCHIZOPHRENIA COMPARED TO HEALTHY CONTROLS. (9th April 2019) - Goldsmith, David; Massa, Nicholas; Pearce, Bradley; Wommack, Evanthia; Alrohaibani, Alaaeddin; Goel, Neha; Cuthbert, Bruce; Fargotstein, Molly; Weng, Lei; Miller, Andrew; Duncan, Erica
Abstract: Background: Previous data have demonstrated that administration of inflammatory cytokines or their inducers leads to altered basal ganglia function associated with reduced psychomotor speed. Patients with schizophrenia (SCZ) exhibit psychomotor slowing and cognitive impairments. Increased inflammatory markers are seen in some patients with SCZ compared to healthy controls (CON). Previous work has reported relationships between inflammatory markers and cognitive impairment, though most studies have evaluated a small number of inflammatory markers and/or cognitive tasks. We thus measured a broad array of inflammatory markers in addition to a variety of psychomotor tasks. We hypothesized that there would be associations between inflammatory markers and psychomotor speed in SCZ subjects compared to CON. Methods: 43 patients with SCZ and 29 CON were recruited from the Atlanta Veterans Affairs Medical Center. The following inflammatory markers were measured: tumor necrosis factor (TNF), interleukin (IL)-1beta (IL-1b), IL-6, IL-10, monocyte chemoattractant protein 1 (MCP-1), IL-6 soluble receptor (IL-6sr), IL-1 receptor antagonist (IL-1ra), and TNF receptor II (TNFR2). Principle components analysis (PCA) was used to create factor loadings that were subsequently used in analyses. The following psychomotor tasks were used: Finger Tapping Task (FTT), Reaction Time Task (RTT), Symbol Coding (SC), and Trail Making Test (TMT). T-tests and chi-square tests were performed to test for differences between diagnostic groups. Spearman's rank order correlations were used to test the associations between inflammatory markers and cognitive tasks. Finally, stepwise, backward linear regression models were used to determine the relationship between inflammatory markers and cognition. Results: There were no differences in age, sex or smoking status between SCZ and CON, but the SCZ group had a higher proportion of black individuals (chi square=4.511, p=0.034). Performance was worse in SCZ than CON on FTT (p=0.002) as well as SC and TMT (both p<0.01). SCZ subjects had higher concentrations of IL-1RA compared to CON (t=-2.004, p=0.049), but no other markers differed significantly between groups. In SCZ subjects, higher levels of TNF (p=0.034), IL-1b (p=0.047) and IL-10 (p=0.027) correlated with worse FTT performance. Similarly, higher levels of IL-1b (p=0.033) and IL-10 (p=0.027) correlated with worse TMT performance. The PCA yielded three factors: Factor 1 (TNF, IL-10, MCP-1), Factor 2 (IL-1b, IL-6, IL-1RA), and Factor 3 (IL6sr and TNFR2). In linear regression models, controlling for demographics, smoking, and Toxoplasma gondii IgG serointensity, Factor 1 predicted worse performance on the FTT (p = 0.029) and TMT (p = 0.012). However, factor 3 predicted better performance on the FTT (p = 0.01), RTT(p = 0.000), and SC(p = 0.034). Fewer and less consistent associations were found between inflammatory markers and cognition in CON subjects in both correlations and linear regressions. Discussion: Psychomotor speed and processing speed were significantly worse in SCZ than CON subjects. Inflammatory markers were more predictive of psychomotor slowing in SCZ subjects than in CON. This finding is consistent with prior studies demonstrating that inflammatory stimuli alter basal ganglia function associated with reduced psychomotor speed as well as a recent study demonstrating similar findings in patients with major depressive disorder. As such, this study provides further support that peripheral inflammatory markers in patients with SCZ may contribute to psychomotor slowing. Psychomotor speed may serve as a relevant outcome variable for future studies targeting inflammatory mediators to treat patients with neuropsychiatric disorders such as SCZ.